Some useful methods for measuring the benefits of social science research - Kilpatrick, Henry E., Jr. (International Food Policy Research Institute, 1998)
What are the “returns” to policy-oriented research in the social sciences? One presumes that the positive net benefits to society, or at least a certain segment of society, would be treated as returns, but how does one determine what these benefits are? Clearly benefits to some social science research are available because society continued to fund it, albeit at different levels in different locations and times. This paper cannot fully answer the questions of what it is we seek to measure in any empirical sense, although it will discuss this issue. The returns in the marketplace for social science research are those that exist in the eye of the customer who bears the cost of the research. This paper's primary goal is to offer the client some ways of measuring these returns. It does this with particular emphasis on methods that are often overlooked, even though some of them have been available to the analyst for decades. It also explains some of the costs and benefits of each method and explains how some of them may be used together in order to achieve a higher level of efficacy in measurement.